Management of Waqf Productive in Makassar City (Case Study of Macanda Cattle Village Dompet Dhuafa at South Sulawesi, Indonesia) - Alda, Alda; Suarni, Agusdiwana; Haanurat, A. Ifayani (Universitas Muhammadiyah Makassar, 2022)
The study aims to determine the management of waqf productive in Makassar city (Case Study at Dompet Dhuafa in Macanda Cattle Village, South Sulawesi, Indonesia). The research uses qualitative research methods. The processed data which is the result of interviews with in 2 (two) cattle village managers, 5 (five) livestock farmers, and 3 (three) staff from Dompet Dhuafa, South Sulawesi. The result of the research is that the waqf productive management system through the cattle village program can improve the economy for the beneficiaries, because from raising cattle village, society could be get many things apart from the benefits of the animals that are kept as well as training and assistance from Dompet Dhuafa, South Sulawesi Indonesia. Dompet Dhuafa plays a very important role in the cattle village program therefore it can empower farmers. With the aim of improving the welfare of farmers. The cattle village itself is fully managed by breeders, with assistance in the form of colony cages and livestock. Among them are free-range chickens, chicken pieces, and rabbits for the beneficiaries to be cared for and developed until the number increases. Hence, the livestock are sold so that the sales proceeds are paid to the livestock village companion to get wages as beneficiaries